ANALYSIS OF HANGMAN GAME IMPLEMENTATION FOR HSK TEST PARTICIPANTS USING FLUTTER - Yefta Chrstian; Denissa Denissa (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2022)
Mandarin Chinese, more commonly known as Modern Chinese, is one of the worlds’ many languages. It is the mainofficial language of the People’s Republic of China, and it is also one of the most anticipated languages across the world. In year2020, the Mandarin language is the second most spoken language in the world at 1.12 billion speakers. To facilitate the growinguse of Mandarin in the workplace, more and more private schools are teaching Mandarin as a second language. This leads to a needto assess the expertise of the speakers, which leads to the creation of certain Chinese proficiency tests such as Hanyu ShuipingKaoshi (HSK). To support HSK test takers, the author intends to provide a new kind of media to help the test takers expand theirvocabulary. With the help of Flutter and Firebase Cloud Firestore, the result is an e-learning mobile application, served as ahangman game. Survey results show people are interested in the application and believe that it can help the players expandtheir vocabularies.